Policies as information carriers: How environmental policies may change beliefs and consequent behavior - Ann-Kathrin Koessler; Stefanie Engel (ZBW – Leibniz Information Centre for Economics, 2019)
This paper discusses how policy interventions not only alter the legal and financial framework in which an individual is operating, but can also lead to changes in relevant beliefs. We argue that such belief changes in how an individual perceives herself, relevant others, the regulator and/or the activity in question can lead to behavioral changes that were neither intended nor expected when the policy was designed. In the environmental economics literature, these secondary impacts of conventional policy interventions have not been systematically reviewed. Hence, we intend to raise awareness of these effects. In this paper, we review relevant research from behavioral economics and psychology, and identify and discuss the domains for which beliefs can change. Lastly, we discuss design options with which an undesired change in beliefs can be avoided when a new policy is put into practice.
Keywords: D01; D80; D90; H23; Q58; 330; environmental policies; behavioral economics; beliefs; policy intervention